2006
DOI: 10.1093/fampra/cmi107
|View full text |Cite
|
Sign up to set email alerts
|

Helicobacter pylori test & treat strategy for dyspepsia: a qualitative study exploring the barriers and how to overcome them

Abstract: GPs will need reassurance that test and treat will not lead to missed malignancies. The financial costs and staffing implications of NICE dyspepsia guidance will need to be discussed locally by Primary Care Trusts, microbiology laboratories, gastroenterologists and pharmacy advisors and implemented with local guidance, increased communication and education.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…69 McNulty et al 106 explored the views of primary care about introducing the H. pylori test-and-treat strategy and found that staff preferred stool tests to breath tests, as they impacted less on practice budget and time. On the other hand, stool antigen testing may be somewhat less acceptable to patients.…”
Section: Type Of Diagnostic Methods To Detect H Pylori Infectionmentioning
confidence: 99%
See 1 more Smart Citation
“…69 McNulty et al 106 explored the views of primary care about introducing the H. pylori test-and-treat strategy and found that staff preferred stool tests to breath tests, as they impacted less on practice budget and time. On the other hand, stool antigen testing may be somewhat less acceptable to patients.…”
Section: Type Of Diagnostic Methods To Detect H Pylori Infectionmentioning
confidence: 99%
“…195 Authors who explored the introduction of test-and-treat from the perspective of primary care found that primary care health staff reported that the major barrier to the introduction of NICE test-and-treat guidance for patients with dyspepsia was the time taken to give patients information on testing, test results, and treatment and the impact on nurses' time. 106 …”
Section: Implementation Of Guidelines In Clinical Practicementioning
confidence: 99%
“…Patients might not come back to bring the stool specimen; however, the blood test or UBT can be done before they leave. [74]…”
Section: Preventative Measuresmentioning
confidence: 99%
“…Despite being told the breath test incurred a prescription charge, more respondents preferred the breath test (58%) to stool test (34%). GPs have reported that the breath test is too time-consuming for them to perform routinely in the practice setting 9 and, at 2005 costs, it is also more expensive than the stool test. Half of employed participants took time off from work and 80% required an extra appointment for their blood test.…”
Section: Discussionmentioning
confidence: 99%
“…7,8 GPs have suggested that patients and practices would accept stool testing if appropriately counselled about the improved accuracy over blood serology, and the ease of implementation in the practice setting. 9 There have not been any UK studies examining the acceptability of helicobacter stool tests. Patient compliance with opportunistic faecal occult blood testing in asymptomatic general practice patients reached 56% in a large Birmingham study 10 ; acceptance in symptomatic patients is likely to be much higher.…”
Section: Introductionmentioning
confidence: 99%